2003
DOI: 10.1002/mame.200290037
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Polymer Nanostructures by Injection Molding

Abstract: The nanometer scale topography of self‐assembling structural protein complexes in animals is believed to induce favorable cell responses. An important example of such nanostructured biological complexes is fibrillar collagen that possesses a cross‐striation structure with a periodicity of 69 nm and a peak‐to‐valley distance of 4–6 nm. Bovine collagen type I was assembled into fibrillar structures in vitro and sedimented onto solid supports. Their structural motif was transferred into a nickel replica by physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 30 publications
0
98
0
Order By: Relevance
“…That layer acted as an electrode in the subsequent electroplating process. The shims were plated to a thickness of approximately 300 nm (for more information about the procedure see Gadegaard et al (2003)). The shims were finally trimmed to approximately 30!30 mm sizes using a metal guillotine.…”
Section: Nanopatterning and Die Fabricationmentioning
confidence: 99%
“…That layer acted as an electrode in the subsequent electroplating process. The shims were plated to a thickness of approximately 300 nm (for more information about the procedure see Gadegaard et al (2003)). The shims were finally trimmed to approximately 30!30 mm sizes using a metal guillotine.…”
Section: Nanopatterning and Die Fabricationmentioning
confidence: 99%
“…Flemming et al prepared PMMA replicas of decelluralised blood vessels containing the 3-dimensional structure of the extra cellular matrix (Flemming, Murphy et al 1999). Gadegaard et al demonstrated the ability to replicate the nanometric structure of collagen fibrils and fibres (Gadegaard, Mosler et al 2003). Although, there is a range of alternative technologies available for patterning surfaces for biological applications, the majority of the research is still applying semiconductor techniques such as photolithography and electron beam lithography.…”
Section: Patterning Techniquesmentioning
confidence: 99%
“…The sample is inserted into a tank with nickel ions and when drawing a current a layer of nickel www.intechopen.com can be deposited in the master substrate. This shim will then be fixed in the cavity of the injection moulding tool (Gadegaard, Mosler et al 2003).…”
Section: Replicationmentioning
confidence: 99%
“…A wide range of applications has been explored including microfluidic devices [3,4], diffractive optical elements [5], anti-reflective surfaces [6,7], superhydrophobic surfaces [8][9][10], and functional cell culture substrates [11][12][13][14]. Commercial injection molding is routinely used to replicate features with details down to 150 nm in the case of Blu-Ray discs, while replication demonstrating lateral resolution as low as 5 nm has been demonstrated in research [15][16][17][18][19][20]. This suggests that the lower limit of replication is determined by the structural detail of the mold surface.…”
Section: Introductionmentioning
confidence: 99%